Exploring Customer Views on Digitalized vs. Traditional Restaurants: A Study in the Restaurant Industry - Rahim, Noor Fareen Abdul; Sabeh, Hala Najwan; Binti Ahmad Zaky, Itqan Darwisyah; Naidu, Hemaram Naidu A/L Ramu; Heng, Bee Yen; Laili, Anivia Fatma; Trisnawati, Annisa Bela Ayu; Andrasiuk, Ryhor; Bukhovetskaya, Valeria; Kee, Daisy Mui Hung (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
The restaurant industry has grown widely, not only for local food but for various types of food from other countries. With the fast pace of the technological revolution, the restaurant industry must also keep up with this revolution to remain relevant. Hence, there is the introduction of digitalized restaurants in this industry that have a great debate with traditional restaurants. The main objective of this study is to explore and analyze customer perceptions and views regarding digitalized restaurants compared to traditional restaurants. This study would also help the restaurant industry transform into digitalization that corresponds with customers' views. For research purposes, data collection from a sample of customers who have recently dined in both types of restaurants by conducting a questionnaire targeting at least 100 respondents would be conducted. The questionnaire will focus on gathering data related to customers' perspectives and satisfaction and examining the variables of efficiency and effectiveness and perceived benefits such as convenience, visuals, time consumption, customization, loyalty and rewards programs, and digital feedback. This data would be further analyzed using Statistical Package for the Social Sciences (SPSS). The expected outcome of this study is to provide the restaurant industry with valuable knowledge regarding consumer preferences for digitalized or traditional restaurants. Besides, this study would benefit the restaurant industry in transforming digitalized based on consumers' perceptions and views.